Diel activity patterns of a canopy-inhibiting beetle community (Coleoptera) in a Neotropical rainforest - Kirmse, Susan (Frontiers in Forests and Global Change, 2024)
Diel activity is one main feature of animal`s behavior and is often an intrinsic trait characterizing distinct taxonomic groups. Abiotic conditions such as temperature may influence the diel activity patterns of arthropod communities associated with a particular ecosystem or habitat. On the other handSimilarly, biotic factors, such as resource availability, will impact theaffect arthropod activity of arthropods. In addition, diel activity is thought to be an represent one important factor in niche paortitioning of arthropod communities. As part of a larger beetle survey in a lowland tropical rainforest in southern Venezuela, I analyzed the diel activity of an arboreal beetle community collected on from 23 canopy–tree species during over a cumulative year. Diel activity was observed in 535 beetle species, comprising 5948 individuals on the host trees, using a canopy crane installed in the study area. Of these 535 beetle species, 198 species (37%) showed diurnal activity, and 281 species (52.5%) showed nocturnal activity. In contrast, the proportions of nocturnal (n = 2024, 34%) and diurnal (n = 1983, 33.3%) individuals was were balanced. Most of the observed beetles occurred only during their activity phases ion their host trees. This particularly applies to extrafloral nectaryand flower-visiting beetle species. Flowering trees attracted a different proportions of diurnal and nocturnal species according to the flowering syndrome, whereas. Contrary, extrafloral nectaries were visited mainly visited during theat night. Thus, the beetle communities associated with single tree species showed a distinct compositions of nocturnal and diurnal species.